Governing indigenous territories : enacting sovereignty in the Ecuadorian Amazon - Erazo, Juliet S., 1970- (Duke University Press, 2013)
An ethnography showing that collective land titling for native peoples is both an enormous accomplishment and a source of new expectations, obligations, and subjectivities within the legally established indigenous territories.